Предмет: Математика, автор: Vvanilok

Раскройте скобки и упростите выражение
x-(x-y)
a-(b+a)
(m-n)+n
(x+y)-y
5-(3+x)
-x+(x+2,7)
-(-в+3,8)+0,7
4,74-(2a+3,7)

Ответы

Автор ответа: polinasima432
1

Пошаговое объяснение:

1.х-х+у=у

2.а-б-а=-б

3.m-n+n=m

4.х+у-у=х

5.5-3-х=2-х

6.-х+х+2,7=2,7

7.в-3,8+0,7=в-3,1

8.4,74-2а-3,7=1,04-2а

Автор ответа: nastabutilina5
1

Ответ:

х-(х-у)=х-х+у

а-(b+a)=a-b-a

(m-n)+n=m-n+n=m

(x+x)-y=2x-y

5-(3+x)=5-3-x=2-x

-x+(x+2,7)=-x+x+2,7=2,7

-(-в+3,8)+0,7=в-3,8+0,7=в-3,1

4,74-(2а+3,7)=4,74-2а-3,7=1,04-2а

Похожие вопросы